Human fibrosarcoma cells selected for ultra-high doxorubicin resistance, acquire trabectedin cross-resistance, remain sensitive to recombinant methioninase, and have increased c-MYC expression - Morinaga, Sei; Han, Qinghong; Mizuta, Kohei; Kang, Byung Mo; Bouvet, Michael; Yamamoto, Norio; Hayashi, Katsuhiro; Kimura, Hiroaki; Miwa, Shinji; Igarashi, Kentaro; Higuchi, Takashi; Tsuchiya, Hiroyuki; et al. (Frontiers in Oncology, 2025)
BackgroundDoxorubicin is standard first-line chemotherapy for soft-tissue sarcoma (STS), yet the emergence of resistance severely limits its clinical efficacy. Developing novel strategies to overcome resistance are critical for improving soft-tissue sarcoma patient outcomes.MethodsAn ultra-high doxorubicin-resistant (UHDR) HT1080 fibrosarcoma cell line was established through stepwise exposure to increasing doxorubicin concentrations over 5-months. Over the course of the five months, HT1080 cells were cultured in doxorubicin concentrations that increased stepwise from 8 nM to 15 µM, an 1875-fold increase. Cell viability assays for HT1080 and UHDR were performed using the WST-8 cell-viability agent. c-MYC expression was analyzed by Western blotting.ResultsUHDR-HT1080 cells exhibited an 11.6-fold increase in doxorubicin resistance compared with parental HT1080 cells and displayed selective cross-resistance to trabectedin (8.9-fold), while remaining sensitive to recombinant methioninase (rMETase). rMETase synergistically enhanced doxorubicin efficacy in UHDR cells. Western blotting demonstrated an 8.4-fold elevation in c-MYC expression in UHDR-HT1080 cells.ConclusionThe findings indicate that rMETase can overcome ultra-high doxorubicin resistance in fibrosarcoma cells, likely through targeting methionine addiction, a universal metabolic vulnerability of cancer. These results support the potential clinical application of methionine restriction therapy to treat doxorubicin-resistant STS.